THE IMPACT OF TRADING VOLUME ACTIVITY AND EARNINGS QUALITY ON STOCK RETURN VOLATILITY: DOES MEDIA EXPOSURE PLAY A ROLE? - Isnayni Sabila; Bambang Sutopo (ZILLZELL MEDIA PRIMA, 2025)
The purpose of this study is to investigate the relationship between the volatility of stock returns, trading volume activity and earnings quality, using media exposure as a moderating factor. This research is based on consumer cyclicals sector companies listed on the Indonesian stock exchange during the 2020-2022 period. Panel data regression is used to measure the relationship between trading volume activity, earnings quality, media exposure, and stock return volatility. Empirical findings from this study support that positive earnings quality can reduce stock return volatility. However, for trading volume activity, the interaction between media and trading volume activity, as well as the interaction between earnings quality and trading volume activity proved to have no effect. This study provides new insights into the role of trading volume activity, earnings quality, and media on stock return volatility. Previous research especially often ignores factors external to the firm such as the influence of media exposure. Therefore, this study explores the role of media interactions on stock return volatility.